Factors Affecting the Indonesian Palm Oil Market in Food and Fuel Industry: Evidence from a Time Series Analysis - Bentivoglio, Deborah; Finco, Adele; Bucci, Giorgia (International Journal of Energy Economics and Policy, 2018)
Nowadays, the demand for palm oil has been increasing worldwide. The multipurpose use combined with a market price below makes palm oil an attractive product. Since 2006, Indonesia has been the biggest producer of palm oil in the world, replacing Malaysia as a chief producer. This study develops a simple theoretical model that integrates some of the factor that could influence the production of palm oil in Indonesia in order to establish the issue of cointegration and causality patterns. This analysis examined the relationships among Indonesian palm oil production, soybean oil price, area harvested for palm oil production in Malaysia and palm oil consumption. The finding shows that all variables positively and significantly affect Indonesian palm oil production. However, the ascent of the Indonesian palm oil industry is the result of a combination of several factors, some of which are relating to the palm oil plant itself, others to policy. Keywords: Palm oil, Time series analysis, Indonesia JEL Classifications: C01, C22, Q17, Q18, Q41